Food Safety within the Household: Risk Reduction - Lucianna Grasso; Rachel Silverberg; George L. Baker; Renée M. Goodrich-Schneider; Keith R. Schneider (EDIS)
Food poisoning is common in the United States. The CDC estimates that 48 million Americans acquire foodborne illness every year, many of which were attributed to food preparation occurring in private homes. In 2013, the top five identified bacterial and viral causes of food poisoning attributed to home food preparation were Salmonella, norovirus, shiga-toxin-producing Escherichia coli, Clostridium perfringens, and Campylobacter. This revised 6-page fact sheet outlines the most common food-safety handling mistakes, which are improper food storage, inadequate cooking or reheating temperatures, cross-contamination, and infected food handlers. Written by Lucianna Grasso, Rachael Silverberg, George L. Baker, Renée M. Goodrich-Schneider, and Keith R. Schneider, and published by the Food Science and Human Nutrition Department, November 2015.